Making the Grade in a Portfolio-Based System: Student Performance and the Student Perspective - Nowacki, Amy S. (Frontiers in Psychology, 2013)
Assessment is such an integral part of the educational system that we rarely reflect on its value and impact. Portfolios have gained in popularity, but much attention has emphasized the end-user and portfolio assessment. Here we focus on the portfolio creator (the student) and examine whether their educational needs are met with such an assessment method. This study aims to investigate how assessment practices influence classroom performance and the learning experience of the student in a graduate education setting. Studied were 33 medical students at the Cleveland Clinic Lerner College of Medicine of Case Western Reserve University, a program utilizing a portfolio-based system. The students may elect to simultaneously enroll in a Masters program; however, these programs employ traditional letter grades. Thus creating a unique opportunity to assess 25 portfolio only (P) students and 8 portfolio and grade (PG) students concurrently taking a course that counts for both programs. Classroom performance was measured via a comprehensive evaluation where the PG students scored modestly better (median total scores, 72% P vs. 76% PG). Additionally, a survey was conducted to gain insight into student’s perspective on how assessment method impacts the learning experience. The students in the PG group (those receiving a grade) reported increased stress but greater affirmation and self-assurance regarding their knowledge and skill mastery. Incorporation of such affirmation remains a challenge for portfolio-based systems and an area for investigation and improvement.